Pengaruh digital marketing, word of mouth, dan brand ambassador terhadap brand awareness serta dampaknya pada purchase decision - Nicholas Taurino; Sarwo Edy Handoyo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
In recent years digital shopping is becoming so popular that e-commerce and marketplace popularity rise a lot. This study has the purpose to test the effect of digital marketing, word of mouth, and brand ambassador to purchase decisions and brand awareness, and also the effect of brand awareness to purchase decisions. A total of 171 respondents have used and shopped using the e-commerce app across the Jabodetabek area. The data then will be analyzed using SmartPLS to find the correlation between each variable and find the effect of digital marketing, word of mouth, and brand ambassador on both purchase decision and brand awareness, and also the effect of brand awareness to purchase decision. The results are: 1) Digital marketing affect purchase decision positively and significantly; 2) Word of mouth affects purchase decisions positively and significantly; 3) Brand ambassadors affect purchase decisions negatively and insignificantly; 4) Digital marketing affects brand awareness positively and significantly; 5) Word of mouth affects brand awareness positively and significantly; 6) Brand ambassador affects purchase decision positively but is insignificant; and 7) Brand awareness affects purchase decisions positively and significantly. Dalam beberapa tahun terakhir, digital shopping menjadi sangat popular sehingga menyebabkan e-commerce dan marketplace mengalami peningkatan popularitas. Studi ini dilakukan untuk menguji efek dari digital marketing, word of mouth, dan brand ambassador terhadap purchase decision dan brand awareness serta menguji efek brand awareness terhadap purchase decision. Dengan total 171 responden yang pernah menggunakan aplikasi e-commerce untuk melakukan pembelian online dan berdomisili di wilayah Jabodetabek. Data yang terkumpul kemudian akan dianalisis dengan menggunakan aplikasi SmartPLS untuk menguji hubungan antar variabel dan efek digital marketing, word of mouth, dan brand ambassador terhadap brand awareness dan purchase decision. Hasil yang didapat adalah: 1) Digital marketing berpengaruh positif dan signifikan terhadap purchase decision; 2) Word of mouth berpengaruh positif dan signifikan terhadap purchase decision; 3) Brand ambassador berpengaruh negatif dan tidak signifikan terhadap purchase decision; 4) Digital marketing berpengaruh positif dan signifikan terhadap brand awareness; 5) Word of mouth berpengaruh positif dan signifikan terhadap brand awareness; 6) Brand ambassador berpengaruh positif namun tidak signifikan terhadap brand awareness; dan 7) Brand awareness berpengaruh positif dan signifikan terhadap purchase decision.